"Tacit pedagogy" and "entanglement": practice-based learning and innovation. Issue 4 (27th February 2020) - Derrick, Jay
Abstract : Purpose: This paper argues that the informal dimensions of practice are critical for understanding workplace learning and innovation, but have been under-theorised and under-researched. This paper aims to build on the thinking of Ellström (2010), Billett (2012) and Guile (2014) to account for the emergence of innovation through practice, and propose two new concepts for improving our understanding of innovation as process: "tacit pedagogy" and "entanglement". This argument is evidenced through a recent study of team-working in a high-profile engineering company. Design/methodology/approach: Qualitative interview data was collected on the informal features of organisational culture and work processes supporting innovation, and how these features intersect and interrelate with the formal features and procedures of the organisation. Findings: Three generic modes of team-working practice are identified which, it is suggested, are likely to be associated with innovatory working, and are observable practices available to future researchers. Practical implications: Productive approaches to the organisation of work processes so as to enhance practitioner learning and the potential for innovation are evidenced and evaluated. Originality/value: The concepts "tacit pedagogy" and "entanglement", intended to improve theoretical understanding of learning and innovation through practice, are introduced.